SOME GENERALIZED TRIPLE SEQUENCE SPACES OF REAL NUMBERS - Debnath, S.; Sarma, B.; Das, B. C. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2015)
The idea of difference sequence spaces was first introduced by Kizmaz in 1981 and the idea of triple sequences was first introduced by Sahiner et.al. 2007. In this article we introduce the notion of triple sequence spaces c_0^3(Δ), c^3(Δ) and l_∞^3(Δ) using the difference operator Δ. We study some of their algebraic and topological properties and prove some inclusion results.